Inflammatory Colitis after Treatment of Melanoma with Talimogene Laherparepvec (T-VEC) - Jennifer Gardner; Teresa Hyun; Gideon Steinbach; John Thompson (Journal of Immunotherapy and Precision Oncology, 2018)
Talimogene laherparepvec (T-VEC) is an intralesional oncolytic viral therapy for the treatment of recurrent, unresectable cutaneous, subcutaneous, and nodal melanoma. It is thought to work through direct tumor oncolysis and by eliciting a tumor-specific systemic immune response. Immune-related adverse events have been reported only rarely with this therapy. We report a case of culture-negative, biopsy-proven colitis following pathologic complete response of recurrent, and intransit cutaneous melanoma to T-VEC. To the best of our knowledge, this is the first report of immune-related colitis following T-VEC.